THE PRACTICE OF AEROBICS AS ADDITIONAL TREATMENT IN ELDERLY MEN DIAGNOSED WITH LUMBAR DISC HERNIATION (Fiep Bulletin - online, 2014)
This work aimed to show how the practice of water aerobics can help in the treatment of lumbar disc herniation in elderly men as well as significant improvements in activities of daily living (ADL) and his conception of quality of life. This study was conducted at the Municipal Sports located in Caieiras / SP, the periods from February to June 2013, where 12 men were selected elderly patients aged 60 years.For data collection we used three assessment instruments: a) adaptation to the physiotherapy evaluation of the lumbar spine used by the Department of Physical Therapy and Speech Therapy and Occupational Therapy, University of São Paulo (USP), composed of 18 questions, 10 questions closed and eight open b) raising test straight leg c) adaptation of the model physical and functional assessment of the spine used by the School of Nursing of Ribeirão Preto (USP), consists of five items: identification, general signs and symptoms , postural and ergonomic aspects, psychosocial and economic aspects, specific signs and symptoms. The data showed a significant improvement in the test straight leg, where 10% were able to exceed 70 degrees, improvements in the relief of pain, the ADV and psychological aspects.
Keywords: old man; aerobics; lumbar disc herniation